Pengaruh Media Augmented Reality Terhadap Pemahaman Konsep Siswa Kelas Xi MIPA SMAN 1 Pujut Pada Materi Asam Basa - Husnusshaliha, Baiq Ulfa; Muti'ah, Muti'ah; Savalas, Lalu Rudyat Telly; Supriadi, Supriadi (FKIP University of Mataram, 2025)
This study aims to determine the effect of Augmented Reality media on the conceptual understanding of eleventh-grade students at SMAN 1 Pujut on the topic of acids and bases. The research design used is a quasi-experiment with a nonequivalent control group design. The population for this study consists of tenth-grade students at SMAN 1 Pujut. The research sample includes class XI F1 as the experimental group (23 students) and class XI F2 as the control group (20 students). The learning outcome instrument is a post-test in the form of multiplechoice questions. Quantitative data analysis was performed to test the hypothesis using a t-test. The results show that the calculated t-value (3,84) is greater than the table t-value (2.01), which means that the null hypothesis (H₀) is rejected, and the alternative hypothesis (Hₐ) is accepted. The results of the student response questionnaire to the application of Augmented Reality learning media on acid-base material showed that the number of students who stated Strongly Agree (SS) was 44%, Agree (A/S) was 34%, Disagree (D/TS) was 17%, and Strongly Disagree (SD/STS) was 5%. Thus, the average percentage of Strongly Agree and Agree choices was 78%. Therefore, it can be concluded that there is an effect of using Augmented Reality media on the conceptual understanding of eleventh-grade students at SMAN 1 Pujut.